1982
DOI: 10.1007/bf00121120
|View full text |Cite
|
Sign up to set email alerts
|

An analysis of vertical velocity spectra obtained in the bomex fair-weather, trade-wind boundary layer

Abstract: Spectra of vertical velocity fluctuations measured on board an aircraft flying over the sea along and across the wind during the Barbados Oceanographic and Meteorological Experiment (BOMEX) are stratified and composited according to estimates of the Monin-Obukhov stability length.This was done to test the hypothesis that a hierarchy of physical mechanisms, responding to wind shear and buoyancy, is active in the turbulent transfer processes of the oceanic subcloud layer. Despite the possibility that the data co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
96
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 109 publications
(106 citation statements)
references
References 44 publications
9
96
1
Order By: Relevance
“…Furthermore, we find a spread in the development of cloud streets depending on the magnitude of the prescribed Q net , with correlation ratios ranging from 1 to 5. The fact that buoyancy-driven cloud street organization is favored in slightly unstable conditions (low sun) compared to stronger instabilities (high sun) agrees well with observations (e.g., Woodcock, 1942;Priestley, 1957;Grossman, 1982;Weckwerth et al, 1997).…”
Section: Without Wind: U = 0 M S −1supporting
confidence: 88%
See 1 more Smart Citation
“…Furthermore, we find a spread in the development of cloud streets depending on the magnitude of the prescribed Q net , with correlation ratios ranging from 1 to 5. The fact that buoyancy-driven cloud street organization is favored in slightly unstable conditions (low sun) compared to stronger instabilities (high sun) agrees well with observations (e.g., Woodcock, 1942;Priestley, 1957;Grossman, 1982;Weckwerth et al, 1997).…”
Section: Without Wind: U = 0 M S −1supporting
confidence: 88%
“…Following Grossman (1982), "At some point (increasing the wind speed/shear) the shearing becomes strong enough so that dynamic instability may interact with buoyancy to produce a hybrid roll vortex/convective cell mechanism. As the shear becomes stronger, shearing instability or roll vortex motion is predominant."…”
Section: Introductionmentioning
confidence: 99%
“…High values of Àz i =L are associated with free convection and the existence of cellular pattern consistent with thermals, and low values of Àz i =L are associated with forced convection and in some cases, the existence of roll circulations. Grossman (1982) observed that roll circulations tended to form when Àz i =L was less than 21.4. Most of other previous studies (e.g., Deardor¤ 1972;LeMone 1973;Sykes and Henn 1989) showed that their criterions for Àz i =L were smaller than that of Grossman (1982), suggesting that roll circulations will be dominant within a slightly unstable mixed layer.…”
Section: Discussionmentioning
confidence: 96%
“…The previous studies have shown that an optimal combination of buoyancy and vertical wind shear is important for the existence of roll circulations in the mixed layer (e.g., Deardor¤ 1972;Grossman 1982;LeMone 1973;Sykes and Henn 1989). They used the Monin-Obukhov length L and the ratio Àz i =L, where z i is the depth of the mixed layer, to define the necessary conditions for the occurrence of roll circulations.…”
Section: Discussionmentioning
confidence: 99%
“…The present analysis and the common presence of rolls in other cold-air outbreak studies suggests the presence of rolls or rolls+cells. Also, the strong winds and surface buoyancy flux combined with the unusually shallow ABL depth would likely put the present case in the ABL depth/Obukhov length regime associated with rolls+cells, or less likely, rolls, rather than pure cellular convection (Grossman, 1982). Note that roll-cell patterns are often referred to as rolls in the literature, because they produce well-defined cloud lines if the updrafts on the crosswind sides of the cells merge into clearly-defined bands of updraft air.…”
Section: Discussionmentioning
confidence: 87%